The Role of Cash Conversion Cycle Components in Determining Profitability - Ghofir, Ade (Sean Institute, 2025)
This study aims to investigate the role of cash conversion cycle components, namely Account Receivable Days, Account Payable Days, and Inventory Days., in determining the profitability of manufacturing companies in the plastic and packaging sub-sector listed on the Indonesia Stock Exchange. Profitability is measured using the Return on Assets (ROA) indicator. Utilizing a quantitative approach, this research applies purposive sampling to select companies that consistently publish annual financial reports during the observation period. The analysis employs multiple linear regression, supported by classical assumption tests to ensure the robustness of the model. The findings demonstrate that each component of the cash conversion cycle affects profitability differently. Account Receivable Days tend to have a negative relationship with profitability, suggesting longer collection periods may hinder performance. Conversely, Account Payable Days show a potential positive influence, indicating that extended payment terms may support liquidity and profitability. Inventory Days also play a significant role, contingent upon the company's operational efficiency. These insights are valuable for financial managers and investors in optimizing working capital management strategies to enhance overall profitability.